CamITree: a streamlined software for phylogenetic analysis of viral and mitochondrial genomes - Sun, Peng; Yang, Yu; Yuan, Mengjie; Tang, Qin (BMC bioinformatics, 2025)
Background Over the past decade, the continuous and rapid advances in bioinformatics have led to an increasingly common use of molecular sequence comparison for phylogenetic analysis. However, the use of multi-software and cross-platform strategies has increased the complexity of phylogenetic tree estimation. Therefore, the development and application of streamlined phylogenetic analysis tools are growing in significance in the field of biology. Particularly for genomes with relatively short sequences, there is a lack of simple and integrative tools for phylogenetic analysis. Results In this study, we present CamlTree (Concatenated alignments maximum-likelihood tree), a user-friendly desktop software designed to simplify phylogenetic analysis for viral and mitochondrial genomes, ultimately facilitating related research. CamlTree provides a workflow including gene concatenation (or coalescence), sequence alignment, alignment optimization, and the estimation of phylogenetic trees using both maximum-likelihood (ML) and Bayesian inference (BI) methods. CamlTree was written in TypeScript and developed using the Electron framework. It offers a primarily user-friendly interface based on the React framework. Conclusions CamlTree software has been released for the Windows OS. It integrates several popular analysis tools to optimize and simplify the process of estimating polygenic phylogenetic trees. The establishment of software can assist researchers in reducing their workload and enhancing data processing efficiency, enabling them to expedite their research progress. The software, along with a detailed user manual, is available at https://github.com/BioCrossCoder/camltree .